Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Loyalitas Karyawan Pada PT. Mahakam Kencana Intan Padi Surabaya - Bahtiar Kertiyasa; Sulastri Irbayuni (Journal of Economic, Bussines and Accounting (COSTING), 2022)
According to the researchers' observations, there are problems related to employee loyalty, therefore the purpose of this study is to determine whether the work environment and compensation affect employee loyalty at PT. Mahakam Kencana Intan Padi Surabaya. The research method used is quantitative. The population in this study were all permanent employees at PT. Mahakam Kencana Intan Padi Surabaya as many as 38 employees. The sampling technique used was the saturated sampling method. The data used in this study is primary data, primary data is obtained from distributing questionnaires, while the data analysis technique uses Partial Least Square (PLS) with SmartPLS software. The results of this study indicate that the work environment and compensation have a positive and significant effect on employee loyalty at PT. Mahakam Kencana Diamond Rice Surabaya. This shows that the existence of a good work environment and compensation will create strong employee loyalty to each employee. Keywords : Work Environment, Compensation, Employee Loyalty